Composition and Distribution of Income Among the Sheep Heahing Nomads - Chauhan, S K (Annals of Arid Zone, 2016)
Farmers of the tribal area of Chamba district in Himachal Pradesh are mainlydependent on sheep rearing for their livelihood which significantly contributetowards the total household income. The variability in agriculturalincome was quite high on small farms compared to medium and large farms.However, the income variability registered reduction with the introduction ofsheep rearing. Relatively more uniform distribution of income was observedin case of large farms.